Calvin on preaching - Schulze, L.F. (Hervormde teologiese studies, 1998)
After introducing the congregation of Geneva to whom Calvin preached, the topic of this paper is discussed under the headings of three questions namely: Why did he preach? How did he preach? and, What did he preach? By answering these questions Calvin's view on preaching is elucidated.